Some issues on the correlation between wage income and labour productivity - Rica Ivan; Calin Tanase Ladar (Agora International Journal of Economical Sciences (AIJES), 2021)
In Romania, both the business environment stakeholders and the academics consider that the path on reaching the average level of development of the European Union and implicitly the adoption of the Euro currency, can be achieved only by improving the standard of living that is the citizens' income, which can be reached only by increasing labour productivity. One of the objectives of the European Union is to reduce the disparities between regions, as confirmed by the evolution of GDP/ capita in the less prosperous Eastern Europe countries in comparison with the more developed EU Members States from Western Europe. There are a number of factors impacting the labour productivity and wage incomes, and the onset of the COVID 19 pandemic has accelerated the adoption of automation, digitalisation and remote work, which will significantly contribute to the disappearance of less skilled jobs and the consolidation of those who are highly qualified ones, the latter being less sensitive to the adoption of new technologies.~~~~~~~~~~~~~~
Keywords: 330